Design of energy use rights trading policy from the perspective of energy vulnerability. (January 2022) - Pan, Yuling; Dong, Feng
Abstract: This paper takes Sichuan Province (China) as an example to improve the design of energy use rights trading policy (ERTP) with the goal of reducing regional energy vulnerability. The following contributions are made to improve the ERTP: (1) The first step in designing the ERTP is to set the total energy consumption target, and this paper formulates the total energy consumption of Sichuan Province in 2025 with reference to China's 14 th Five-Year Plan. (2) This paper adopts the historical egalitarianism, economic egalitarianism, efficiency allocation model and the Game-Equity Fixed Cost Allocation Model (Game-EFCAM) to allocate energy use quotas at the sectoral level. Therein, Game-EFCAM is an allocation model which considers both equity and efficiency. (3) In designing the trading mechanism, this paper exogenizes the price of energy use rights within the quotas and endogenizes (determined by the market) the price of energy use rights outside the quotas. Moreover, this paper adopts a recursive dynamic computable general equilibrium (CGE) model to simulate the effects of different allocation schemes and economic development levels on energy vulnerability. The results show that regional energy vulnerability is minimized under the allocation results of Game-EFCAM. This paper not only improves the ERTP, but also provides a reference for other countries in energy dilemmas. Highlights: The ERTP is broken down into specific mathematical and economic models. Game-EFCAM is the best allocation method for energy use quotas. The implementation of ERTP can reduce energy vulnerability. The implementation of ERTP requires supporting policies.